Ritual Malam 1 Suro dalam Konteks Kebudayaan Jawa: Analisis atas Mitos dan Praktik Spiritual di Desa Mojopahit Lampung Tengah - Aryanti, Adelia Rahma (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
One of the traditions that is still preserved by the Javanese people to this day is the celebration of Malam Suro. This tradition is a commemoration of the Islamic New Year 1 Muharram which has a mystical, sacred and symbolic meaning. The study discusses how to implement the tradition of malam satu suro from a Javanese cultural perspective. This tradition is closely related to the myths and beliefs of the Javanese people. Malam Suro Satu is believed to bring a calm, peaceful and serene life. When carrying out the Suro Satu Malam ritual tradition, it is believed that blessings will come down from the Almighty for those who celebrate it in the form of a thanksgiving. This tradition is carried out from generation to generation from ancestors and then preserved from generation to generation. Research Objectives This aims to understand the meaning and symbolism of the Malam Satu Suro tradition in the context of Javanese people's lives. The specific objectives are to describe the phenomena, events, and perceptions associated with this tradition, and to analyze how this tradition functions as a means to strengthen the cultural and spiritual identity of the Javanese people. This study uses a qualitative descriptive method: This study uses a qualitative descriptive approach, which aims to describe the phenomena, events, social activities, attitudes, and perceptions of the community related to the Malam Satu Suro tradition. Data Collection Techniques Documentation: Data is collected through relevant documents. Researchers collect, identify, and analyze documents to obtain the necessary information. Analysis and Synthesis: After the data is collected, researchers conduct analysis and synthesis to understand the meaning and context of the information obtained.